(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The advantage of the reserpine model in the development of parkinsonian syndrome in experimental animals was shown: symptoms appeared as early as 2 h after reserpine administration and persisted for up to 3 days. Injection of reserpine at a dose of 3 mg/kg, quite clearly influenced behaviour. Significant changes in biochemical indicators, markers of oxidative stress, accompanying disorders of motor functions of experimental animals were revealed. The possibility of correcting the pathology with the help of some agents of antioxidant nature has been shown. Despite the lack of clarity regarding the efficacy of succinate, tocopherol, the study showed that the use of goji berries significantly reduces the risk of Parkinson’s disease.